2022
DOI: 10.1002/anbr.202200089
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐Based Differences in the Biodistribution of Nanoparticles and Their Effect on Hormonal, Immune, and Metabolic Function

Abstract: Males and females respond differently to medications due to physiologic, metabolic, and genetic factors. At times, sex‐related differences cannot be mitigated by dose adjustment to body mass, and are evident from the tissue level to the single cell. The rising number of clinically approved nanotechnologies calls for assessing how their activity is affected by the patient's sex. Herein, sex differences in nanotechnology are scoped, with emphasis on molecular considerations. Sex‐specific pharmacokinetics of nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 132 publications
0
9
0
Order By: Relevance
“…The influence of sex hormones on these responses may involve direct actions on innate immune cells or indirect modulation by other immune or non-immune cells responding to sex hormones [ 39 ]. The influence of hormones, specifically testosterone and oestrogens, has been shown to play a role in modulating immunological responses, leading to variations in adaptive immunity, T-lymphocyte function, and helper-inducer cell activity [ 40 , 41 ]. It has also been observed that male hormones promote a tendency towards cell-mediated immune responses, while female hormones tend to promote humoral immunity [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The influence of sex hormones on these responses may involve direct actions on innate immune cells or indirect modulation by other immune or non-immune cells responding to sex hormones [ 39 ]. The influence of hormones, specifically testosterone and oestrogens, has been shown to play a role in modulating immunological responses, leading to variations in adaptive immunity, T-lymphocyte function, and helper-inducer cell activity [ 40 , 41 ]. It has also been observed that male hormones promote a tendency towards cell-mediated immune responses, while female hormones tend to promote humoral immunity [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…One major factor that must be investigated is the effect of the lipid nanoparticles since they both comprise a significantly different set of lipid nanoparticle (LNP) components 27 . Some LNP formulations have a slower clearance in women than in men, and phagocytosis and macrophage activation are stronger in females than in males 28 (28). Furthermore, an LNP-mRNA formulation showed a stronger inflammatory reaction in female rabbits than in males 29 .…”
Section: Discussionmentioning
confidence: 99%
“…To demonstrate the biodistribution of TET-CTM/L in the NIR in vivo imaging system, 43,44 all various celastrol treatments were labeled as DiD+TET, DiD/C-MEs, TET-DiD/L, and DiD-C-MEs/L, DiD were adopted to act as controls. [33][34][35][36][37][38] DiD group exhibited almost no accumulation at the tumor site between 1~8 h, and the fluorescence intensity was weaker in contrast to other Did treatments.…”
Section: Biodistributionmentioning
confidence: 99%